2014
DOI: 10.1097/icl.0000000000000006
|View full text |Cite
|
Sign up to set email alerts
|

PROSE for Irregular Corneas at a Tertiary Eye Care Center

Abstract: PROSE device is a very useful alternative for irregular corneas to improve visual acuity, to improve comfort, and for symptomatic relief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 11 publications
3
18
0
2
Order By: Relevance
“…Moderate to severe complications of neurotrophic keratopathy can be managed with scleral support contact lenses (Prosthetic Replacement of the Ocular Surface Ecosystem, PROSE). 75, 76 PROSE lenses should be removed after 12 hours. Patients often require assistance to insert or remove the lenses due to poor dexterity.…”
Section: Ophthalmological Treatmentsmentioning
confidence: 99%
“…Moderate to severe complications of neurotrophic keratopathy can be managed with scleral support contact lenses (Prosthetic Replacement of the Ocular Surface Ecosystem, PROSE). 75, 76 PROSE lenses should be removed after 12 hours. Patients often require assistance to insert or remove the lenses due to poor dexterity.…”
Section: Ophthalmological Treatmentsmentioning
confidence: 99%
“…63,67,79,80,87,91,93,99,100,118,126 Other studies reported the number of patients who experienced an improvement of at least two lines of Snellen acuity. Improvements in visual acuity were reported in patients wearing scleral lenses for all indications.…”
Section: Case Reports/retrospective Case Seriesmentioning
confidence: 99%
“…Cotter and Rosenthal 69 Rosenthal et al 70 Rosenthal and Cotter 71 Rosenthal and Croteau 72 Jacobs and Rosenthal 73 Gungor et al 74 Lin et al 75 Lim et al 76 Grover et al 77 Gumus et al 78 Rathi et al 79 Baran et al 80 Cressey et al 81 Kalwerisky et al 82 Rathi et al 83,84 Dimit et al 85 Gire et al 86 Lee et al 87 Lim et al 88 Ling et al 89 Samimi et al 90 Arumugan et al 91 Ciralsky et al 92 Heur et al 93 Mahadevan et al 94 Rose K (Blanchard Contact Lens, Manchester, NH)…”
Section: Case Reports/retrospective Case Seriesmentioning
confidence: 99%
See 2 more Smart Citations